PENGARUH STRUKTUR KEUANGAN, STRUKTUR MODAL, PROFITABILITAS, DAN GOOD CORPORATE GOVERNANCE TERHADAP KEPATUHAN PEMENUHAN KEWAJIBAN PERPAJAKAN PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK JAKARTA - Akhmad Mukhatob (Media Riset Akuntansi, Auditing & Informasi, 2007)
This research attempts to validate financial factors such asfinancial structure, capital structure, and pmfitability and application of good corporate governance on influencing tax compliance on entries listed in Jakarta Stock Exchange over the period 2001-2005 The research also aims to show us how those factors influence tax compliance. This research focuses on selected entities researched by International Institute for Corporate Governance (IICG) based on purposive sampling methods. This research provides description of the level of the tax compliance based on determined attributes and indicators of the entities dassffied by entities' sector as well as their maforilyownership. These estimations will describe which classifications are more comply with government regulation especially on tax laws. A Pearson correlation and a multiple regression model is used to estimate the influence offinancial factors and corporate governance on tax compliance byapplying 5% probability error. The results descriptively reveal that entities which concern in mining sector found as the most comply entffies on tax regulation. Based on majonly ownership, public ownership majority found as the worst tax compliance. By using Pearson Correlation analysis, this research showth at financial structure and capital structure influence insignificantly on tax compliance. Contrary, profitability and good corporate governance influence significantly on tax compliance. Furthermore, regression model shows that independent variables' regression coefficient, financial structure and cap talstnldureinsignilcantlydescnbedependentvariable, tax compliance. On the otherhand, independent variables' regression coefficient, good corporate governance and profit- abiliy, significantly describe dependent variable, tax compliance except forfinancial strudure and capital structure.Keywords: financial structure, capital structure, good corporate governance, profitability tax compliance